Probing substrate binding to the metal binding sites in metallo-β-lactamase L1 during catalysis12. Issue 1 (11th January 2016) - Aitha, Mahesh; Al-Adbul-Wahid, Sameer; Tierney, David L.; Crowder, Michael W.
Abstract : RFQ-EXAFS studies were used to probe the metal centers in metallo-β-lactamase L1 during catalysis. Abstract : Metal ions in metallo-β-lactamases (MBLs) play a major role in catalysis. In this study we investigated the role of the metal ions in the Zn1 and Zn2 sites of MBL L1 during catalysis. A ZnCo (with Zn(ii ) in the invariant Zn1 site and Co(ii ) in the Zn2 site) analog of MBL L1 was prepared by using a biological incorporation method. Extended X-ray absorption fine structure (EXAFS) spectroscopic studies were used to confirm that the ZnCo analog was prepared. To study the roles of the Zn(ii ) and Co(ii ) ions during catalysis, rapid freeze quench (RFQ)-EXAFS studies were used to probe the reaction of the ZnCo-L1 analog with chromacef when quenched at 10 ms, 50 ms, and 100 ms. The L1-product complex was also analyzed with EXAFS spectroscopy. The data show that the Zn–Co distance is 3.49 Å in the resting enzyme and that this distance increases by 0.3 Å in the sample that was quenched at 10 ms. The average Zn–Co distance decreases at the other time points until reaching a distance of 3.58 Å in the L1-product complex. The data also show that a Co–S interaction is present in the 100 ms quenched sample and in the L1-product complex, which suggests that there is a significant rearrangement of product in the active site.